(untitled) (Al-Qamar, 2022)
This study investigates the domains of time management practices utilized by 250 school heads in seven southern districts of KP. Specifically, the study focuses on practices related to scheduling contacts, managing meetings, delegating tasks, handling paperwork, establishing priorities, and managing interruptions. A researcher-designed questionnaire was employed to assess the school heads’ perception levels regarding these domains of time management practices. The questionnaire underwent appropriate validation procedures, and its reliability coefficient was determined to be 0.81. The population for this study consisted of 670 school heads, with the questionnaire being distributed among 250 school heads, of which 172 provided suitable responses. Findings indicate that a majority of school heads (49%) perceived establishing priorities as having a significant impact on their professional attitudes, while the domain with the lowest impact was managing paperwork (23%). These results emphasize the importance of school heads engaging in effective planning and scheduling of both short and long-term goals to fulfill the school’s mission. Furthermore, it is recommended that in-service school heads participate in refresher courses, workshops, and seminars focused on enhancing their time management skills. School heads should also prioritize efficient time allocation for various school activities.